A large scale study on the characterisation of drop-in within a DNA laboratory. (December 2017) - Moore, D.; Liley, J.; Thomson, J.
Abstract: Forensic DNA analysis has become increasingly sensitive in recent years with the advent of improved PCR chemistries and highly sensitive CE instruments. This has allowed the detection of STR alleles from single copies of template DNA. As a consequence of this increased sensitivity and increases in the number of loci tested; understanding and characterising drop-in events become of greater importance. Drop-in is defined by the DNA commission of the International Society of Forensic Genetics as; one or two alleles that "come from different individuals"[1] . Many models have been developed to describe drop-in that can be applied to a continuous probability. However, no large study of drop-in has been published within the literature.